Fine property-tuning through Ca content control in a facile synthesis of glasses-based self-setting injectable hydrogel. (1st December 2021) - Wu, Bing; Pascu, Elena I.; Brady, Sarah A.; Brougham, Dermot F.; Clarkin, Owen M.
Graphical abstract: Highlights: A facile process was created for preparing particulate glass NPs. Initial Ca content affect the morphology and composition of the glass NPs. Setting kinetics of NPs-based hydrogels is influenced by NPs' morphology. Mechanical strength of composite hydrogels can be tailored by Ca content. Abstract: Self-setting injectable composite hydrogels are promising materials in tissue engineering. In this study a facile synthetic approach was designed based on traditional sol–gel method to produce particulate calcium aluminosilicate-type glasses, which were then formulated with potassium alginate to form a self-setting injectable hydrogel. In order to control the setting-time and mechanical properties of the composite materials, a series of samples were produced with different starting chemical composition. The change in chemical composition and morphology of the glass particles in response to varying initial Ca 2+ content were further elucidated by a combination of EM, XRF and NMR spectroscopy, revealing that the binary aluminosilicate glass was preferably formed when low Ca content (<20%) was used in the formulation. At higher Ca content (>30%), calcium aluminosilicates were predominantly formed due to the change in the type of zeolite precursor formed during the low temperature nucleation process in the sol–gel approach. It was also found the hardening times of the alginate gels was positively correlated to the mole ratio of Ca/Al due to high acid resistance of high coordination number Al species. For hydrogels made with glass particle additions, the mechanical strengths were also positively correlated with the Ca/Al ratio for all formulations.